A replication of "The role of intermediaries in facilitating trade" (Journal of International Economics, 2011) - Jianhua Duan; Qian Xuefeng; Kuntal K. Das; Laura Meriluoto; W. Robert Reed (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
This study replicates Ahn, Khandelwal, and Wei's (2011) model of intermediary trade. The study produces two main results. First, the authors are able to reproduce empirical evidence for AKW's three main predictions for Chinese exports. This is impressive because much of the data for their replication are independently sourced. However, when the authors subject their model to additional tests, they find that the evidence is not robust. Using more recently available data to test AKW's first prediction, the authors estimate coefficients that are wrong-signed and significant. When they re-analyze the evidence supporting the second and third predictions, they find that the full sample results mask significant heterogeneity across Chinese regions. In many cases, key coefficients are insignificant. In a few cases, they are wrong-signed and significant. Finally, using multiple versions of a key variable measuring the number of required import documents by country, the authors discover that the results are not robust across versions.
Keywords: F1; 330; intermediaries; exports; productivity; heterogeneous firms; China